BENTUK DAN FUNGSI KATEGORI FATIS DALAM BAHASA MELAYU - Zia Hisni Mubarak; Aldriani Yessie (IdeBahasa, 2019)
The objective of this study was to find out the form and function of phatic words in Malay language of Kepulauan Riau. Phatic word is the word that does not have any information or ideas in it. This study was a qualitative study. To collect the data, it used some informants. The informants were the Malay teenagers who lived in Batam. Then, informants were interviewed and recorded during the interview session. From the data, it was found some phatic categories such as phatic particles (lah, kan, pun, sih, nah, kah), phatic words (halo, ayok, ya, yak, iye, yeh, ye, tu, tuh, cam, macam, gitu, oi, wei, eh, weh), phatic phrases (assalamualaikum, insyaallah), and phatic integration (cam tu lah, gitu lah, cam.. sih, nah gitu). It was also found the phatic function such as the way to break, to prove, to confirm, to affirm, to convince, to start and end the conversation.